Synthetic biology and microbioreactor platforms for programmable production of biologics at the point-of-care - Pablo Perez-Pinera (Nature Portfolio, 2016)
Current biopharmaceutical manufacturing platforms use single biologic-producing cell lines cultured at large scales. Here the authors develop a small-scale, portable biomanufacturing platform to produce single dose IFNa2b and rHGH from a single engineered strain of P. pastoris.